2010
DOI: 10.1111/j.1468-1293.2010.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the possible influence of hepatitis C virus and liver fibrosis on HIV type 1 immunological and virological outcomes

Abstract: ObjectivesThe aim of the study was to evaluate the possible effect of hepatitis C virus (HCV) coinfection on the viroimmunological outcomes of HIV-1 infection. MethodsA cross-sectional study of 805 patients with active HCV infection receiving or not receiving antiretroviral therapy (ART) was carried out. ResultsA number of parameters were significantly associated with undetectable HIV-1 viral load in univariate analyses, such as age, toxic habits, CD4 cell count, liver test results, HCV viral load and ART. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…In line with previous reports, we found that older age and better adherence to HIV therapy were associated with HIV SVS [11,17]. Furthermore, excessive alcohol consumption, which is a known predictor of poor adherence to HAART, was associated with failure to achieve HIV SVS in our univariate analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports, we found that older age and better adherence to HIV therapy were associated with HIV SVS [11,17]. Furthermore, excessive alcohol consumption, which is a known predictor of poor adherence to HAART, was associated with failure to achieve HIV SVS in our univariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…However, chronic hepatitis C is an independent risk factor for severe antiretroviral hepatotoxicity, with a three-fold higher risk of grade 3 or 4 transaminitis [7][8][9]. Despite the higher risk of HAART hepatotoxicity in this population, most studies have not shown a negative impact of HCV infection on HIV virologic control [10,11]. However, most of these studies compared HIV-monoinfected patients with HIV/ HCV-coinfected patients and did not examine the influence of HCV-related variables such as liver fibrosis, HCV genotype, viral load, transaminase levels and HCV RNA positive on HIV sustained viral suppression (SVS) [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence on the prognostic role of HIV residual viremia (2.5-50 copies/ml) [19], and we cannot exclude the possibility that residual viremia may influence HCV RNA viral load, as could greater HIV burden. No correlation was observed between CD4+ cell count and HCV RNA values as previously described [12]; CD4+ cell count increased from T1 to T2 (mean increase of 78 cells/mm 3 , p  = 0.003). The baseline immunocompetence in our enrolled patients was greater than that reported for subjects in the study by Grint et al 576 cells/mm3 versus 340 cells/mm 3 in the subjects on ART [13].…”
Section: Discussionsupporting
confidence: 61%
“…In a cross-sectional study by Collazos et al [12], HCV RNA load was lower in subjects with undetectable HIV viremia (6.17 log 10 IU/mL versus 6.08 log 10 IU/mL, p = 0.03), whereas Grint et al [13] demonstrated that only ongoing HAART is a predictive factor of HCV viral load stability over time, with an increase of 2.6% per year compared to 27.6% in untreated subjects ( p  = 0.009). Plasma HIV viremia is a dynamic variable; patients taking antiretroviral therapy (ART) may develop virological breakthrough or experience side effects leading to treatment interruption, and untreated subjects may start antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown that HCV co-infection is associated with either smaller CD4 increases after initiation of ART [11-16] or a delayed CD4 response [17], other studies report early detected differences in CD4 response wane over time [4, 18]. Many studies have not found such an association [3, 19-25]. Most of the aforementioned studies did not report on or find any association between HCV/HIV co-infection and subjects' HIV-1 virologic responses [12, 13, 26].…”
Section: Introductionmentioning
confidence: 99%